MSX2 Gene Duplication in a Patient with Eye Development Defects. (9th December 2015) - Plaisancié, Julie; Collet, Corinne; Pelletier, Valerie; Perdomo, Yaumara; Studer, Fouzia; Fradin, Mélanie; Schaefer, Elise; Speeg-Schatz, Claude; Bloch-Zupan, Agnès; Flori, Elisabeth; Dollfus, Hélène
Abstract: Background : MSX2 mutations are a very rare cause of craniosynostosis. Gain-of-function mutations may lead to the Boston-type craniosynostosis with limb defects and refraction errors, whereas loss-of-function mutations causes primary osseous defects such as enlarged parietal foramina. Materials and Methods : Herein we report the case of a child with bicoronal synostosis and cutaneous syndactylies, who presented iridal and chorioretinal colobomas. Due to the craniofacial features that were prominent in the clinical picture, the genes involved in craniosynostosis were explored. Results : The patient disclosed an intragenic duplication of the entire MSX2 gene whereas no mutation was identified in any major genes known to be involved in craniosynostosis. Conclusion : This is the first report of an eye development defect due to an increase in the MSX2 copy number in a human being. The implication of this gene in eye development has already been shown in several animal models. Indeed, overexpression of the Msx2 gene in a mouse model resulted also in optic nerve aplasia and microphthalmia. This report expands the phenotypic spectrum of the MSX2 mutations impacting early ocular development knowledge.